Oviductal extracellular vesicles from women with endometriosis impair embryo development - Li, Yuehan; Cai, Lei; Guo, Na; Liu, Chang; Wang, Meng; Zhu, Lixia; Li, Fei; Jin, Lei; Sui, Cong (Frontiers in Endocrinology, 2023)
Objective To investigate the influence of oviductal extracellular vesicles from patients with endometriosis on early embryo development. Design In vitro experimental study Setting University-affiliated hospital. Patient(s) Women with and without endometriosis who underwent hysterectomy (n = 27 in total). Intervention(s) None. Main Outcome Measure(s) Oviductal extracellular vesicles from patients with endometriosis (oEV-EMT) or without endometriosis (oEV-ctrl) were isolated and co-cultured with two-cell murine embryos for 75 hours. Blastocyst rates were recorded. RNA sequencing was used to identify the differentially expressed genes in blastocysts cultured either with oEV-EMT or with oEV-ctrl. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were performed to identify potential biological processes in embryos that oEV-EMT affects. The functions of oEV on early embryo development were determined by reactive oxygen species (ROS) levels, mitochondrial membrane potentials, total cell numbers, and apoptotic cell proportions. Result(s) Extracellular vesicles were successfully isolated from human Fallopian tubal fluid, and their characterizations were described. The blastocyst rates were significantly decreased in the oEV-EMT group. RNA sequencing revealed that oxidative phosphorylation was down-regulated in blastocysts cultured with oEV-EMT. Analysis of oxidative stress and apoptosis at the blastocysts stage showed that embryos cultured with oEV-EMT had increased ROS levels, decreased mitochondrial membrane potentials, and increased apoptotic index. Total cell numbers were not influenced. Conclusion(s) Oviductal extracellular vesicles from patients with endometriosis negatively influence early embryo development by down-regulating oxidative phosphorylation.